(untitled) (INNOVATIVE ECONOMY, 2022)
Grosul V.A., Usova M.A. STRATEGIC ASPECTS OF RISK RESISTANCE MANAGEMENT OF A RETAIL ENTERPRISE Purpose. The aim of the article is substantiation of the methodology of strategic management of risk resistance of a retail enterprise. Methodology of research. The works of domestic and foreign scientists on strategic risk management in the enterprise are the theoretical and methodological basis of the study. The tasks set in the work were solved using the following methods: analysis and generalization - when analysing models of strategic risk management; a systematic approach, an abstract and logical one - when determining the main stages of strategic management of the risk resistance of a retail enterprise, developing a “bow tie” diagram for assessing the risks of a retail enterprise; economic and mathematical modelling - when developing a tuple of structural elements of an information system for managing the risk resistance of a retail enterprise. Findings. Scientific approaches to the formation of a strategic enterprise risk management system were studied. The key aspects of the methodology “Risk management of the organization. Integrated Model” were considered. A PPRR-model of strategic management of the risk resistance of a retail enterprise was developed. The main stages of strategic management of the risk resistance of a retail enterprise are determined. A tuple of structural elements of the information system for managing the risk resistance of a retail enterprise was formed. A methodical approach to the construction of a “bow tie” diagram for risk assessment of a retail enterprise is substantiated. This approach takes into account the relationship between the sources of risk and the consequences of its implementation. Originality. An organizational and methodological approach to the formation of a strategic management system for the risk resistance of a retail enterprise has been developed, unlike existing ones, it creates the opportunity to quickly and timely respond to changes in the external environment, identify sources of risk, establish cause-and-effect relationships between risk factors and its consequences, analyse and prove relevant information at risk for strategic decision makers. Practical value. Practical implementation of the results of the study lies in the development of applied tools that can be used to make informed strategic decisions to mitigate the consequences of the onset of risk events, increase the level of risk resistance of retail enterprises under resource and time constraints, while contributing to the achievement of the set targets for the activities of a trading enterprise. Key words: risk, risk resistance, strategic management, PPRR model, information system, assessment, “bow tie” diagram.